Necesidad de reformar la Ley Orgánica de Empresas Públicas con respecto al pago de tasas de uso del espacio público por parte de las empresas del Estado - Torres Romero, Sonia Katherine (2015)
Property of public use, are the heritage of the State and as such should be managed properly by the authorities, ensuring sustainable development and rational use of these, established through the National Assembly that these financial resources generating and imposing taxes to pay for the use and enjoyment of these, whether by natural or legal persons. The Constitution of the Republic of the Ecuador in its Art.300 determines "the tax system will be governed by the principles of generality, progressiveness, efficiency, administrative simplicity, non-retroactivity, equity, transparency and revenue adequacy. The direct and progressive taxation priority will be given. Tax policy will promote the redistribution and stimulate employment, the production of goods and services, and responsible environmental, social and economic behavior." These principles are of general character, its scope is for all people who have ability to contribute; the escalation has to do with the fact of who else has, more pay. While that administrative simplicity, it implies that the tax must be carried in a simple way the taxpayer time and money-saving. But mainly establishes the obligation of the payment of taxes. Before this the Art.301 of the same body of law cites "only at the initiative of the Executive function and by law passed by the National Assembly, it may establish, modify, release or extinguish tax. Only by legislative act of competent body is you can set, modify, exonerate and extinction rates and contributions. Rates and special contributions are created in accordance with the law". I.e., that only the function Executive, by means of law discussed and approved by the National Assembly, may create, modify, exonerate or extinguished only by Act of authority municipality, Provincial Council, taxes, or other bodies designated by law may create, modify, exonerate, and extinction rates, these will be created in accordance with law. Likewise, the tax code determines in its Art.1 that "" the precepts of this Code regulating legal relations coming of tributes, among active subjects and taxpayers or persons in charge of those. Shall apply to all national, provincial, municipal or local taxes or other creditor entities of the same, as well as to the situations that arise or relate to them". According to the provisions, the scope of the tax code includes the imposition, collection of all national taxes, taxes provincial national, municipal and provincial taxes, taxes contributions special or improved municipal character, or other creditors of tax bodies, as well as the situations that arise, or derived from them. Now, the organic code of Territorial Organization, autonomy and decentralization in its Art.417 determines that "are assets for public using those whose use by consumers is direct and general, free of charge. However, they may also be exclusive and temporary use on payment of a royalty. At this and in contrast or contradiction, mainly the COOTAD, the organic law of public enterprises determines that "public enterprises applies for the tax regime corresponding to the entities and agencies from the public, including sector of exemptions, provided for in the tax code, in the law of taxation internal and other laws of nature tax. For the above-mentioned companies can benefit from the designated regime it is required that are registered in the single register of taxpayers, take accounting, and fulfill the other formal duties referred to in the tax code, this law and other laws of the Republic. "Public companies that provide public services shall be exempt from the payment of royalties, taxes or any other consideration for the use or occupation of public space or public roads and Airspace State, regional, provincial or municipal, for placement of structures, poles and routing networks". What causes discomfort and discontent since citizenship, if both the Constitution of the Republic, the tax code, the organic code of Territorial Organization, autonomy and decentralization determine the payment of taxes, in this case rate for the use of public space, pointless exempt public companies, possessing legal capacity and as such responsibilities and tax obligations. Hence it is necessary to carry out a legal research - criticism on this issue, which is carried out a legal reform to the public companies Act, is consistent with the regulations in force, especially with the Constitution and to ensure respect for the rights of the people, without causing evil with this economic and promoting good live